2014
DOI: 10.11646/phytotaxa.181.1.2
|View full text |Cite
|
Sign up to set email alerts
|

Towards a natural classification of Dothideomycetes 7: The genera Allosoma, Austropleospora, Dangeardiella, Griggsia and Karschia (Dothideomycetes incertae sedis)

Abstract: This is the seventh of a series of papers in which we report on re-examination of herbarium types of Dothideomycetes genera, incertae sedis. By examining and re-describing the generic types which are not previously illustrated or are poorly described, we attempt to propose their familial and higher placement according to the morphology based on modern taxonomic concepts. In this paper the type specimens of Allosoma, Austropleospora, Dangeardiella, Griggsia and Karschia were re-examined and are illustrated. An … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Barr (1979) placed Karschia in Patellariaceae Corda. Then it was transferred to Lichenotheliaceae, Lichenotheliales by Thambugala et al (2014a) based on the morphology observed from herbarium material. Ertz & Diederich (2015) reexamined the type specimen and sequenced the type species.…”
Section: Resultsmentioning
confidence: 99%
“…Barr (1979) placed Karschia in Patellariaceae Corda. Then it was transferred to Lichenotheliaceae, Lichenotheliales by Thambugala et al (2014a) based on the morphology observed from herbarium material. Ertz & Diederich (2015) reexamined the type specimen and sequenced the type species.…”
Section: Resultsmentioning
confidence: 99%
“…Genera marked with ( # ) refer to changes made via articles in the same journal volume and annotated under the family or order (i.e. Ariyawansa et al 2014c; Boonmee et al 2014b; Hongsanan et al 2014c; Thambugala et al 2014c; Phookamsak et al 2014). In the present outline, we have added ( C ) = coelomycetous and ( H ) = hyphomycetous asexual genera against entries where known.…”
Section: Methodsmentioning
confidence: 99%
“…Notes: Lumbsch and Huhndorf (2010) listed Allosoma under Dothideomycetes , genera incertae sedis . Thambugala et al (2014c) refer Allosoma to Englerulaceae based on morphological similarities with the generic type of Englerulaceae .…”
Section: Notes On Recent Changes and Namingmentioning
confidence: 99%
See 2 more Smart Citations